Soluble glutamic-pyruvic transaminase,esterase D.,nucleoside phosphorylase and placenta acid phosphatase in Malaysia. - Tan, Soon Guan; Teng, Yao Sheng (1977)
Healthy blood donors from the National Blood Bank,Kuala Lumpur were electrophoretically phenotyped for red cell s-Gpt,esterase D and nucleoside phosphorylase. Placental samples from the Maternity Ward,General Hospital,Kuala Lumpur were electrophoretically phenotyped for acid phosphatase.s-Gpt and esterase D were found to be polymorphic in Malaysians of Malay,Chinese and Indian ancestries. 325 Malays,204 Chinese and 215 Indians were phenotyped for s-Gpt . The most common phenotypes for all three ethnic groups are phenotypes 1,2-1 and 2. One Malay and one Chinese showed the rare phenotype 6-2. The gene frequencies are Malays,Gpt1=0.343,Gpt2=0.655;Chinese Gpt1=0.471,Gpt2=0.527;Indians,Gpt1=0.437,Gpt=0.563. 184 Malays,211 Chinese and 115 Indians were phenotyped for esterase D. Malays and Indians showed only phenotypes 1,2-1 and 2 while one Chinese showed phenotypes 3-1. The gene frequencies are Malays,EsD1=0.658,EsD2=0.342;Chinese,EsD1=0.597,eSd2=0.401;Indians EsD10.735,EsD2=0.265. No variant from the usual phenotypes was observed among 269 Malays,81 Indians and 58 Chinese phenotyped for red cell nucleoside phosphorylase and 219 Malays,122 Indians and 245 Chinese phenotyped for plaental acid phosphatase.